Pengaruh Tingkat Suku Bunga, IHK, PDB Real Estate Terhadap Harga Properti di Indonesia Periode Tahun 2010-2016 - Adeyatni, Meta (PPJP ULM, 2018)
This research unducted to (1) analyze the influence of interest rate, consumer priceindex, a gross domestic product of real estate in Indonesia, (2) to know the mostdominant factor influencing property price in Indonesia in 2010-2016. The Scope ofthis research is Indonesia as the research area. The data sources of this research comefrom secondary data that will processing using multiple regression analysis by F-test(simultaneously) and T-tes (Partially). The research’s result proves that simultaneouslygross domestic bruto of real estate is influencing property prices. And partiallyconfirms of real estate and consumer price index are impacting property pricesignificantly.